2013
DOI: 10.1016/j.jadohealth.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Intergenerational Continuity in Harsh and Abusive Parenting: The Importance of a Nurturing Relationship With a Romantic Partner

Abstract: Purpose Harsh, abusive and rejecting behavior by parents toward their children is associated with increased risk for many developmental problems for youth. Earlier research also shows that children raised by harsh parents are more likely to treat their own children harshly. The present study sought to identify behaviors of romantic partners that might help break this intergenerational cycle of child mistreatment. Methods Data come from the Family Transitions Project, a 22-year, 3-generation study of a cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 23 publications
3
68
0
3
Order By: Relevance
“…In other studies, factors that influence the development of positive parenting skills for resilient children include the presence of a sensitive mother, the development of social competence, and the establishment of satisfactory love-relationships (Conger, Schofield, Neppl, & Merrick, 2013; Raby, Steele, Carlson, & Sroufe, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In other studies, factors that influence the development of positive parenting skills for resilient children include the presence of a sensitive mother, the development of social competence, and the establishment of satisfactory love-relationships (Conger, Schofield, Neppl, & Merrick, 2013; Raby, Steele, Carlson, & Sroufe, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, multiple longitudinal studies have found that individuals whose own parents were harsh, rejecting, uncaring, or controlling are more likely to parent their own children in a similar manner (e.g., Belsky, Jaffee, Sligo, Woodward, & Silva, 2005; Conger, Schofield, Neppl, & Merrick, 2013; Friesen, Woodward, Horwood, & Fergusson, 2013; Kovan, Chung, & Sroufe, 2009; Neppl, Conger, Scaramella, & Ontai, 2009). However, despite the robustness of these findings, not all parents treat their children the way their own parents treated them.…”
Section: Cross-generational Transmission Of Parenting and Gene-enviromentioning
confidence: 99%
“…Such a possibility could occur if genetic variants shape the context of parental care in ways that render parents more likely to rely on parental care they themselves received as a model. Only a handful of studies have examined variables that interact with the intergenerational transmission of parenting, finding that the age at which the parents had children (Belsky, Hancox, Sligo, & Poulton, 2012), marital quality and the level of support and nurturance from the spouse toward the parent (Conger, Schofield, Neppl, & Merrick, 2013; Wang et al, 2014), and the spouse’s parenting of the child (Conger, Schofield, & Neppl, 2012) interact with the parenting received by participants in predicting their own parenting behavior. Evidence also suggests the nurturing behaviours of others in the parent’s life (Jaffee et al, 2013; Schofield et al, 2013), and the child’s gender interact with the parenting received by participants in predicting their own parenting, although these findings are mixed (see Conger et al, 2009).…”
Section: Cross-generational Transmission Of Parenting and Gene-enviromentioning
confidence: 99%
“…Competence within the peer group reflects the formation of social skills—such as empathy, perspective-taking, and conflict resolution—that are thought to be fundamental for close relationships during adulthood, including the parent-child relationship (Collins & van Dulman, 2006; Hartup, 1996; Sroufe, Egeland, Carlson, & Collins, 2005a). In addition, adults’ romantic relationships are thought to serve several, overlapping functions that are relevant to the task of providing supportive parental care, including providing opportunities to practice providing and receiving care for others, regulating positive and negative emotions that may carry over into the parent-child relationship, buffering the adult from stresses emanating from outside the family, and modeling parental behavior as a co-parent (Ainsworth, 1989; Belsky & Jaffee, 2006; Conger, Schofield, & Neppl, 2012; Conger, Schofield, Neppl, & Merrick, 2013; Grych, 2002; Krishnakumar & Buehler, 2000). Indeed, longitudinal investigations have provided evidence that individuals’ experiences with both peers and romantic partners may mediate the intergenerational continuities in positive parenting (Caspi & Elder, 1988; Chen & Kaplan, 2001; Chen, Liu, & Kaplan, 2008; Kerr et al, 2009; Shaffer et al, 2009).…”
mentioning
confidence: 99%